2015
DOI: 10.1155/2015/859730
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activities of Mononuclear Ruthenium(II) Coordination Complexes

Abstract: Ruthenium compounds are highly regarded as potential drug candidates. The compounds offer the potential of reduced toxicity and can be tolerated in vivo. The various oxidation states, different mechanism of action, and the ligand substitution kinetics of ruthenium compounds give them advantages over platinum-based complexes, thereby making them suitable for use in biological applications. Several studies have focused attention on the interaction between active ruthenium complexes and their possible biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 102 publications
1
73
0
Order By: Relevance
“…The pH dependent UV-Vis spectra in In order to get a deeper insight into the formation of the intermediate species 1 H NMR spectra were recorded at various pH values (Fig. 6), which also refer to the presence of more than one kind of hydrolysis products.…”
Section: Speciation Studies Of [Ru II (η 6 -(2-phenoxyethanol))(bpy-rmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH dependent UV-Vis spectra in In order to get a deeper insight into the formation of the intermediate species 1 H NMR spectra were recorded at various pH values (Fig. 6), which also refer to the presence of more than one kind of hydrolysis products.…”
Section: Speciation Studies Of [Ru II (η 6 -(2-phenoxyethanol))(bpy-rmentioning
confidence: 99%
“…During the last two decades a significant amount of work has been published in the field of ruthenium metallodrugs for application as anticancer agents due to the relevant cytotoxicity exhibited by many of these compounds against several cancer cell lines [1][2][3][4][5]. Particular attention has been given to the families of the so called piano-stool geometries where the stool is formed by the 'η 5 -C 5 H 5 ' or 'η 6 -C 6 H 6 ' bonded to the ruthenium centre and the three legs are represented by sigma coordinated ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Ruthenium-based complexes are some of the most promising, with reported selective potency in vitro and in vivo. [17][18][19][20][21][22] McGowan et al have synthesised a range of ruthenium metal complexes for their uses as anticancer agents. [23][24][25][26] The work published on ruthenium quinaldamides showed that under inert atmosphere conditions, the filtering over NH4PF6 yielded the ruthenium quinaldamide monomers.…”
Section: Introductionmentioning
confidence: 99%
“…18 As listed in Table 2, although a large number of Ru complexes have shown great promise as potential antitumor agents, only three complexes, NAMI-A, KP1019, and NKP1339 (Table 3), have entered clinical trials. 16,19,20 Clinically, all the three complexes exhibited promising anticancer activities with minimal side effects; an ideal property of a good anticancer drug (Table 3). In addition, these complexes have octahedral coordination geometry with respect to the Ru(III) metal center; however, they exhibit different biological activities despite their structural and chemical similarities.…”
mentioning
confidence: 99%
“…In addition, these complexes have octahedral coordination geometry with respect to the Ru(III) metal center; however, they exhibit different biological activities despite their structural and chemical similarities. 19 Recently, 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-functionalized Ru(II) polypyridyl complexes were screened for their efficiency as theranostic photosensitizers for cancer treatment. 21 The presence of a redox-sensitive TEMPO moiety enhanced the intracellular fluorescence of TEMPOfunctionalized Ru(II) complexes in photodynamic treatment, which was observed using confocal microscopy and flow cytometry.…”
mentioning
confidence: 99%